2014
DOI: 10.1098/rspb.2014.0454
|View full text |Cite
|
Sign up to set email alerts
|

Trans-generational immune priming in honeybees

Abstract: Maternal immune experience acquired during pathogen exposure and passed on to progeny to enhance resistance to infection is called trans-generational immune priming (TgIP). In eusocial insects like honeybees, TgIP would result in a significant improvement of health at individual and colony level. Demonstrated in invertebrates other than honeybees, TgIP has not yet been fully elucidated in terms of intensity and molecular mechanisms underlying this response. Here, we immune-stimulated honeybee queens with Paeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 43 publications
4
73
1
3
Order By: Relevance
“…2010), woodlice (Roth & Kurtz 2009), and fruit flies (Pham et al . 2007), as well as trans-generationally primed honeybees (Hernández López et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2010), woodlice (Roth & Kurtz 2009), and fruit flies (Pham et al . 2007), as well as trans-generationally primed honeybees (Hernández López et al . 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is conflicting evidence as to the protective mechanism of priming once these eggs hatch and the larvae develop, with some studies showing a continued concentration of antimicrobial peptides (Barribeau et al . 2016; Sadd & Schmid-Hempel 2007), some suggesting a differentiated cellular response (Hernández López et al . 2014), and some implicating an inducible transcriptional program (Trauer-Kizilelma & Hilker 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Our analyses showed that while the results obtained from TER studies are largely consistent with our theoretical predictions, the signal is much less clear for TEI studies. We believe that an integrative view of the transgenerational immune memory requires both approaches [17,18,21,62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Sadd et al, 2005;Moret, 2006;Sadd and Schmid-Hempel, 2007;Roth et al, 2010;Hernández López et al, 2014). Although these studies remove the effect of pathogen multiplication and possible vertical transmission, injection is an unnatural exposure route and it is not clear how relevant these studies are to actual pathogen infection.…”
Section: Introductionmentioning
confidence: 95%